Editor’s Note - Wetmore, Tom (Current Musicology, 2017)
Issue 101 of Current Musicology presents five articles that exemplify the journal’s commitment to critical discussions of music and sound across the disciplines. In her article, “As Time Goes By: Car Radio and the Travel Experience in Twentieth-Century America,” Sarah Messbauer explores the advent of car radio in the United States during the first half of the twentieth century. Tracing car radio’s transformation from an object of suspicion—often evoking fears of distracted driving—to a near-ubiquitous feature of the automobile experience, Messbauer elucidates deep links between the evolution of car radio and a constellation of associated shifts in the cultural experience and practice of space and time. Such changes include fundamental alterations of human geography through patterns of routinized travel, evolving methods of disciplining industrial labor, and shifting patterns of mass production and consumption. Sarah Kirby’s article, “Cosmopolitanism and Race in Percy Grainger’s American ‘Delius Campaign,’” analyzes Grainger’s early-twentieth-century campaign to promote the works of Frederick Delius in the United States, exposing the campaign’s underpinnings in Grainger’s racist, nativist, and eugenicist ideologies and projects. Kirby exposes a peculiar construction of cosmopolitanism at the root of Grainger’s modes of presenting Delius to US audiences, arguing that by downplaying his European national roots, Delius and his music could be deployed as a “blank canvas” upon which Grainger could superimpose his own “developing racist ideologies.” The issue’s third article, Alison Maggart’s “Milton Babbitt’s Glosses on American Jewish Identity,” outlines the evolution of Babbitt’s engagement with Jewish themes over the course of his career, arguing for the centrality of the Jewish Exile narrative to the composer’s discourse and music. In Babbitt’s articulation of the narrative, Maggart argues, Schoenberg is often framed as the prophet Moses, the United States as the Promised Land, and the university as the site of refuge or asylum. Babbitt thus “interweaves the plight of American academic composers with that of the Jewish people in ancient, recent, and contemporary history.” Maggart supports her historical work with a theoretical analysis of three key moments in Babbitt’s Glosses (1988). Brendan Kibbee’s article, “Black Labor and the Deep South in Hurston’s The Great Day and Ellington’s Black, Brown, and Beige,” highlights the representation of the laboring black body in two landmark works by Zora Neale Hurston and Duke Ellington. Kibbee frames the emphasis on black labor as a form of resistance to predominant representations of Deep South life at the time of their premieres. Indebted to legacies of blackface minstrelsy, such representations tended to present Southern plantation life in nostalgic and racist framings. Building on the writings of Cedric Robinson and Raymond Williams, Kibbee argues that Hurston’s and Ellington’s pieces critically reimagine the Deep South landscape, exposing the ideological work entailed in the construction of race and space. A more recent topic is found in Erol Koymen’s article, “From Coups that Silence Ezan-s to Ezan-s that Silence Coups!: Sonic Resistance to the 2016 Turkish Military Coup.” Koymen argues that Islamic calls to prayer, mediated by electroacoustic amplification and internet social networking, forged Turkish citizens into a “synchronized, collectivized body politic” that resisted the military coup by occupying urban streets and squares. By filling secular urban spaces with sacred sounds, Koymen asserts, these events underline the importance of sound to an “epochal neo-Ottoman shift in Turkish politics.” Indeed, by altering the meanings and feelings associated with various urban spaces, these events “embedd[ed] the materiality of sound and sonically disciplined bodies into the stone and concrete of urban spaces, thus transforming them and Turkey’s public sphere.” This issue would have been impossible without the exemplary work of the entire editorial board and advisory team, especially Didier Sylvain, my predecessor as editor and closest collaborator, and Paula Harper, the reviews editor for this issue. I also wish to single out the exceptional work of the team of Associate Editors that worked particularly hard in bringing this publication to fruition: Jesse Chevan, Kyle DeCoste, Mike Ford, Jane Forner, Julia Hamilton, and Ian Sewell.